Islamic Republic of Afghanistan : 2017 Article IV Consultation and Second Review under the Extended Credit Facility Arrangement, and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Afghanistan. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the real GDP of Afghanistan grew by 2.4 percent in 2016 thanks to higher agricultural output. For 2017, growth is projected at 2.5 percent and at 3 percent for 2018. This is below the rate of growth needed to reduce unemployment, and is contingent on an improvement in confidence, implementation of reforms, and continued strong donor support. Consumer price inflation remains moderate and is expected to average 6 percent in 2018. Afghanistan has also made progress in strengthening the country's anti-corruption framework, and its efforts in antimonetary laundering and counter financing of terrorism resulted in the recent exit from the Financial Action Task Force's monitoring process.